Preparation method of long-acting heat storage controllable heat release phase change material

By combining the crystallization characteristics of sugar alcohol phase change materials and the control effect of hydrogel frame materials, a long-term heat storage and controllable heat release phase change material was prepared, which solved the problems of easy loss of latent heat and uncontrollable heat release of existing phase change materials, and achieved efficient and controllable heat storage and heat release effects.

CN119529771AActive Publication Date: 2025-02-28CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411726710.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing phase change materials are prone to loss of latent heat during heat storage, the heat release is uncontrollable, and there is a risk of leakage.

Method used

By comprehensively utilizing the crystallization characteristics of sugar alcohol phase change materials and the control of the molecular movement of phase change materials by hydrogel framework materials, the crystallization rate and supercooling stability of phase change materials are regulated, and a long-term heat storage and controllable heat release phase change material was prepared. The material stores the latent heat of high temperature at room temperature for a long time and can controllably release the latent heat of phase change under external stimulation.

Benefits of technology

It realizes long-term efficient heat storage and controlled heat release of phase change materials, avoids the risk of volatile and leakage of latent heat, and has good photothermal conversion capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529771A_ABST
    Figure CN119529771A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage materials, and particularly relates to a long-acting heat storage and controllable heat release phase change material and a preparation method thereof. According to the long-acting heat storage controllable heat release phase-change material, the crystallization rate and supercooling stability of the phase-change material are regulated and controlled by comprehensively utilizing the crystallization characteristic of the sugar alcohol phase-change material and the control effect of the hydrogel framework material on molecular movement of the phase-change material, so that the phase-change material can store high-temperature latent heat for a long time at room temperature; and the stored phase change latent heat can be controllably released under external stimulation. The long-acting heat storage controlled-release heat phase change material can solve the problems that the phase change material needs to be subjected to efficient heat preservation, latent heat is prone to loss, and heat release is uncontrollable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a method for preparing a long-acting heat storage and controllable heat release phase change material. Background Art

[0002] With the development of industry, people's demand for energy is gradually increasing. However, the mismatch between time and space of existing energy utilization technology limits the efficiency of energy utilization. Phase change heat storage technology with phase change materials (PCMs) as heat storage medium is considered to be an effective way to solve the time and space mismatch between supply and demand of intermittent renewable energy, which can greatly improve energy utilization. PCMs used for phase change heat storage should have high phase change latent heat, good phase change kinetics and as small volume change as possible. Therefore, solid-liquid PCMs are the most studied PCMs at present. However, solid-liquid PCMs will repeatedly present liquid state during use, bringing potential leakage risks. For this reason, shaped phase change materials (FPCMs) came into being. FPCMs are formed by adsorbing solid-liquid PCMs in porous support materials. It has the advantages of a wide range of support materials, large phase change latent heat, and easy incorporation of various functional fillers, thus becoming a hot spot in phase change material research in recent years.

[0003] Among the reported PCMs, sugar alcohol PCMs have attracted much attention due to their extremely high latent heat of phase change. The melting temperature of sugar alcohol PCMs is higher than room temperature, so good insulation measures are required to avoid the loss of latent heat. However, the crystallization process of molten sugar alcohols is usually accompanied by obvious supercooling, which makes it possible to maintain the molten state of sugar alcohol PCMs at low cost at room temperature and avoid the loss of latent heat, thus producing a new type of PCMs, namely "space-time phase change materials (SPCMs)". However, supercooling, as a common physical and chemical phenomenon, is not stable and is affected by many factors. Therefore, how to maintain sugar alcohol PCMs in a molten state at room temperature and effectively and controllably induce the crystallization of supercooled molten sugar alcohols to achieve controlled heat release is the key to the development and application of SPCM.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a long-term heat storage and controllable heat release phase change material and a preparation method thereof, so as to solve the problem that the latent heat of the phase change material is easy to lose and the heat release is uncontrollable.

[0006] In order to achieve the above-mentioned purpose of the present invention, the basic idea of ​​the present invention is: comprehensively utilize the crystallization characteristics of sugar alcohol phase change materials and the control effect of hydrogel skeleton materials on the molecular movement of phase change materials, regulate the crystallization rate and supercooling stability of phase change materials, so that they can store high-temperature latent heat for a long time at room temperature, and can controllably release the stored phase change latent heat under external stimulation, and have good photothermal conversion ability.

[0007] According to the above ideas, the preparation method of the long-acting heat storage and controlled heat release phase change material includes the following steps:

[0008] S1. Mix the organic phase change materials in a certain proportion and heat them to 10°C above their phase change temperature to completely melt them;

[0009] S2, adding polyvinyl alcohol to the mixed phase change material and heating until it is completely dissolved;

[0010] S3, adding acrylic acid, N,N-methylenebisacrylamide, ammonium persulfate and filler to the mixed solution, and heating to make it evenly dispersed;

[0011] S4. After several freeze-thaw cycles, the moisture is dried to obtain a long-lasting heat storage and controlled-release thermal phase change material.

[0012] Preferably, in step S1, the organic phase change material is two or more of erythritol, xylitol, sorbitol, mannitol, inositol, and galactitol;

[0013] Preferably, in step S2, the mass ratio of the added amount of polyvinyl alcohol to the phase change material is (0.1-2):1.

[0014] Preferably, in step S3, the mass ratio of the added amount of acrylic acid to the polyvinyl alcohol is (0.05-1):1.

[0015] Preferably, in step S3, the mass ratio of the added amount of N,N-methylenebisacrylamide to the polyvinyl alcohol is (0.05-1):1.

[0016] Preferably, in step S3, the mass ratio of the added amount of ammonium persulfate to the polyvinyl alcohol is (0.05-1):1.

[0017] Preferably, in step S3, the filler is at least one of graphite nanosheets, metal nanowires, carbon nanotubes, graphene, and MXene.

[0018] Preferably, in step S3, the mass ratio of the added amount of filler to the polyvinyl alcohol is (0.05-1):1.

[0019] Preferably, in step S4, the freeze-thaw cycle conditions are: low temperature -197 to -10°C, high temperature 10 to 50°C, and the number of cycles is 1 to 5 times.

[0020] A composite phase change material with controlled heat release properties is prepared by using the above-mentioned method for preparing a long-lasting heat storage controlled heat release phase change material.

[0021] The advantages and positive effects of the long-acting heat storage and controlled heat release phase change material and the preparation method thereof described in the present invention are:

[0022] 1. The present invention uses a variety of sugar alcohol phase change materials for compounding, which ensures that the obtained composite phase change material has the advantages of high latent heat, good supercooling stability and controllable heat release.

[0023] 2. The present invention uses polyvinyl alcohol gel as a skeleton, which can effectively control the motion characteristics of the liquefied phase change material molecules, further improve its supercooling stability and controllable heat release performance, and at the same time ensure the efficient coating of the phase change material, and the obtained material is not easy to leak.

[0024] 3. The preparation process of the present invention is simple, the material source is wide, the repeatability is good, the preparation cycle is short, and it is easy to promote and apply.

[0025] 4. The long-lasting heat storage and controlled heat release phase change material involved in the present invention can solve the problems of phase change materials requiring efficient thermal insulation, easy loss of latent heat, and uncontrollable heat release, and has good light-heat conversion and latent heat storage performance, and can be used in outdoor warmth preservation and thermal management fields.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The DSC curves of the long-acting heat storage controlled-release thermal phase change material and polyol obtained in Example 1, Example 2, and Example 3;

[0028] Figure 2 This is the heat release curve of the long-acting heat storage and controlled heat release phase change material obtained in Example 1 under external mechanical stimulation after being cooled to room temperature. DETAILED DESCRIPTION

[0029] The embodiments of the present invention will be described in detail below in conjunction with examples. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] Example 1

[0031] Add 6.08g xylitol and 1.92g erythritol to a beaker, heat to 115°C and stir thoroughly to mix completely. Add 20ml of deionized water to a beaker, stir to completely dissolve, then add 1g of polyvinyl alcohol, heat and stir in a 95°C water bath until completely dissolved, cool to room temperature, add 1g of acrylic acid, 0.05g of N,N-methylenebisacrylamide and ammonium persulfate, and 0.06g of graphite nanosheets, stir in a 65°C water bath for 5 minutes to disperse evenly, react at a constant temperature for 1h, cool to room temperature, perform three freeze-thaw cycles (freeze at -20°C for 2h, thaw at room temperature for 2h), and after returning to room temperature, dry the water at 105°C to obtain a controlled thermal release composite phase change material.

[0032] Figure 2 This is the heat release curve of the long-term heat storage and controlled heat release phase change material obtained in Example 1 under external force stimulation. When the phase change material is mechanically stimulated, it quickly solidifies and releases latent heat, and the surface temperature of the material rises rapidly. After the mechanical stimulation stops, the heat release and temperature rise gradually stop. Stimulation again can increase the temperature and release heat again. This process can be repeated many times, and the maximum temperature of the sample can reach 38°C.

[0033] The performance of the long-lasting heat storage and controlled-release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 144 J / g, the melting point was 73°C, and the photothermal conversion efficiency was 90%.

[0034] Example 2

[0035] A method for preparing a long-acting heat storage and controlled-release phase change material, except that the feeding amounts of xylitol and erythritol are 5.32 g and 1.68 g respectively, other operation steps are the same as those in Example 1.

[0036] The performance of the long-lasting heat storage and controlled-release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 96 J / g, the melting point was 68°C, and the photothermal conversion efficiency was 87%.

[0037] Example 3

[0038] A method for preparing a long-acting heat storage and controlled-release phase change material, except that the feeding amounts of xylitol and erythritol are 4.56 g and 1.44 g respectively, other operation steps are the same as those in Example 1.

[0039] The performance of the long-lasting heat storage and controlled-release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 72 J / g, the melting point was 65°C, and the photothermal conversion efficiency was 76%.

[0040] Example 4

[0041] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that sorbitol is used instead of xylitol, the other operating steps are the same as those in Example 1.

[0042] The performance of the long-lasting heat storage and controlled-release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 64 J / g, and the melting point was 110°C.

[0043] Example 5

[0044] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that sorbitol and mannitol are used to replace xylitol and erythritol, other operation steps are the same as those in Example 1.

[0045] The performance of the long-lasting heat storage and controlled heat release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 71 J / g, and the phase change temperature was 112°C.

[0046] Example 6

[0047] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that the amount of acrylic acid used is 0.5g, the other operating steps are the same as those in Example 1.

[0048] The performance of the long-lasting heat storage and controlled heat release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 110 J / g, and the phase change temperature was 64°C.

[0049] Example 7

[0050] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that the amount of N,N-methylenebisacrylamide used is 0.01g, the other operating steps are the same as those in Example 1.

[0051] The performance of the long-lasting heat storage and controlled heat release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 74 J / g, and the phase change temperature was 60°C.

[0052] Example 8

[0053] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that the amount of ammonium persulfate used is 0.01g, the other operating steps are the same as those in Example 1.

[0054] The performance of the long-lasting heat storage and controlled heat release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 71 J / g, and the phase change temperature was 63°C.

[0055] Example 9

[0056] A method for preparing a long-lasting heat storage and controlled heat release phase change material, except that the amount of graphite nanosheets used is 0.12g, the other operating steps are the same as those in Example 1.

[0057] The performance of the long-lasting heat storage and controlled heat release phase change material was tested. The liquid phase of the composite phase change material did not leak, the latent heat was 61 J / g, and the phase change temperature was 62°C.

[0058] Example 10

[0059] A method for preparing a long-acting heat storage and controlled heat release phase change material, except that the freeze-thaw cycle temperature is changed from -197°C to room temperature, the other operating steps are the same as those in Example 1.

[0060] The performance of the long-lasting heat storage and controlled heat release phase change material was tested, and the liquid phase of the composite phase change material leaked, with latent heat of 45 J / g and phase change temperature of 80°C.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A long-term heat storage and controllable heat release phase change material, characterized in that: By regulating the crystallization rate and supercooling stability of the phase change material, it can store high-temperature latent heat for a long time at room temperature, and can controllably release the stored phase change latent heat under external stimulation, and has good light-to-heat conversion efficiency, and can be applied to outdoor warmth preservation and thermal management. To achieve the above purpose, the long-term heat storage and controllable heat release phase change material is prepared as follows: S1, mixing the organic phase change material and heating it until it is completely melted; S2, adding polyvinyl alcohol to the mixed phase change material and heating until it is completely dissolved; S3, adding acrylic acid, N,N-methylenebisacrylamide, ammonium persulfate and filler to the mixed solution, heating and making it uniformly dispersed; S4. After several freeze-thaw cycles, the moisture is dried to obtain a long-lasting heat storage and controllable heat release phase change material.

2. The method for preparing the long-acting heat storage and controllable heat release phase change material according to claim 1, characterized in that: In the step S1, the organic phase change material is two or more of erythritol, xylitol, sorbitol, mannitol, inositol, and galactitol.

3. The method for preparing the long-acting heat storage and controllable heat release phase change material according to claim 1, characterized in that: In the step S2, the mass ratio of the added amount of polyvinyl alcohol to the phase change material is (0.1-2):

1.

4. The method for preparing a long-acting heat storage and controllable heat release phase change material according to claim 1, characterized in that: In the step S3, the mass ratio of the added amount of acrylic acid to the polyvinyl alcohol is (0.05-1):1, the mass ratio of the added amount of N,N-methylenebisacrylamide to the polyvinyl alcohol is (0.05-1):1, the mass ratio of the added amount of ammonium persulfate to the polyvinyl alcohol is (0.05-1):1, and the mass ratio of the added amount of filler to the polyvinyl alcohol is (0.05-1):

1.

5. The method for preparing a long-acting heat storage and controllable heat release phase change material according to claim 1, characterized in that: In step S4, the freeze-thaw cycle conditions are: low temperature -197 to -10°C, high temperature 10 to 50°C, and the number of cycles is 1 to 5 times.

6. The method for preparing a long-acting heat storage and controllable heat release phase change material according to claim 1, characterized in that: In step S3, the filler is at least one of graphite nanosheets, metal nanowires, carbon nanotubes, graphene, and MXene.

7. The long-lasting heat storage and controllable heat release phase change material according to claim 1, characterized in that: The long-lasting heat storage and controlled heat release phase change material can solve the problems of phase change materials requiring efficient thermal insulation, easy loss of latent heat, and uncontrollable heat release, and can be applied to fields such as outdoor warmth preservation and thermal management.

8. A phase change material capable of controlled heat release prepared according to the method for preparing a phase change material with long-lasting heat storage and controlled heat release according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Stretchable self-healing hydrogel flexible strain sensor and production method thereof

    CN109294133A

  • Cross-seasonal shape-stabilized phase change energy storage material as well as preparation and application thereof

    CN112940684A

  • Preparation method of phase change heat storage particles

    CN117965139A

  • Shape-stabilized phase change cold storage material with double-network structure and preparation method of shape-stabilized phase change cold storage material

    CN118240270A

  • Process for preparing phase change microcapsule having thermally conductive shell

    US20160151757A1